Biomarkers in Cardiorenal Syndrome and Potential Insights Into Novel Therapeutics - Chung, Edmund Y. M.; Trinh, Katie; Li, Jennifer; Hahn, Sebastian Hayden; Endre, Zoltan H.; Rogers, Natasha M.; Alexander, Stephen I. (Frontiers in Cardiovascular Medicine, 2022)
Heart and kidney failure often co-exist and confer high morbidity and mortality. The complex bi-directional nature of heart and kidney dysfunction is referred to as cardiorenal syndrome, and can be induced by acute or chronic dysfunction of either organ or secondary to systemic diseases. The five clinical subtypes of cardiorenal syndrome are categorized by the perceived primary precipitant of organ injury but lack precision. Traditional biomarkers such as serum creatinine are also limited in their ability to provide an early and accurate diagnosis of cardiorenal syndrome. Novel biomarkers have the potential to assist in the diagnosis of cardiorenal syndrome and guide treatment by evaluating the relative roles of implicated pathophysiological pathways such as hemodynamic dysfunction, neurohormonal activation, endothelial dysfunction, inflammation and oxidative stress, and fibrosis. In this review, we assess the utility of biomarkers that correlate with kidney and cardiac (dys)function, inflammation/oxidative stress, fibrosis, and cell cycle arrest, as well as emerging novel biomarkers (thrombospondin-1/CD47, glycocalyx and interleukin-1β) that may provide prediction and prognostication of cardiorenal syndrome, and guide potential development of targeted therapeutics.